2022
DOI: 10.2169/internalmedicine.8241-21
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Differences between Eosinophilic Esophagitis and Asymptomatic Esophageal Eosinophilia

Abstract: Objective According to consensus guidelines, eosinophilic esophagitis (EoE) is defined as a clinicopathological entity whose symptoms and histology must always be considered together. However, endoscopic findings typical of EoE are often seen in asymptomatic esophageal eosinophilia (aEE). We aimed to clarify the clinicopathological features of aEE. Methods We retrospectively compared cases of aEE and those of symptomatic EoE. Patients or MaterialsWe reviewed 146 patients who underwent upper gastrointestinal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…We did not use the diagnosis code DK20.9D for EoE in the current study, as it was introduced in Denmark as late as 2014, and still not routinely used. Furthermore, recent studies have reported on asymptomatic oesophageal eosinophilia (aEE), which has endoscopic and histological findings similar to those of EoE, but does not have oesophageal dysfunction 28,29 . EoE and aEE may have the same pathogenesis, but it is still unclear if aEE should be treated or not, and further investigation is needed 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We did not use the diagnosis code DK20.9D for EoE in the current study, as it was introduced in Denmark as late as 2014, and still not routinely used. Furthermore, recent studies have reported on asymptomatic oesophageal eosinophilia (aEE), which has endoscopic and histological findings similar to those of EoE, but does not have oesophageal dysfunction 28,29 . EoE and aEE may have the same pathogenesis, but it is still unclear if aEE should be treated or not, and further investigation is needed 29 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 EoE and aEE may have the same pathogenesis, but it is still unclear if aEE should be treated or not, and further investigation is needed. 29 When using the broad definition, we may include patients with aEE, although most of the patients undergoing an upper gastrointestinal endoscopy will have upper gastrointestinal symptoms as an indication for the procedure. A limitation of our study is that in the cases where no symptoms were registered, we cannot know if the patients were truly asymptomatic or whether symptoms were not registered by the physician.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several findings, such as multiple polypoid lesions [ 79 , 80 , 81 ], tug sign/pull sign [ 82 , 83 ], ankylosaurus back sign [ 84 ], and caterpillar sign [ 49 ] have been reported. In addition, endoscopic abnormalities have been localized in small areas of the lower end of the esophagus, or with patchy distribution in 30–40% of patients [ 85 , 86 ] ( Figure 8 ). Such localized types may be missed, unless the whole esophagus is carefully observed with proper expansion by both air inflation and deep inspiration during endoscopy.…”
Section: Other Endoscopic Findings Suggestive Of Eoementioning
confidence: 99%